Gold Nanoshelled Liquid Perfluorocarbon Nanocapsules for Combined Dual Modal Ultrasound/CT Imaging and Photothermal Therapy of Cancer. Issue 6 (5th February 2014) - Ke, Hengte; Yue, Xiuli; Wang, Jinrui; Xing, Sen; Zhang, Qian; Dai, Zhifei; Tian, Jie; Wang, Shumin; Jin, Yushen
<x xml:space="preserve">Abstract</x> The integration of multimodal contrast‐enhanced diagnostic imaging and therapeutic capabilities could utilize imaging guided therapy to plan the treatment strategy based on the diagnostic results and to guide/monitor the therapeutic procedures. Herein, gold nanoshelled perfluorooctylbromide (PFOB) nanocapsules with PEGylation (PGsP NCs) are constructed by oil‐in‐water emulsion method to form polymeric PFOB nanocapsules, followed by the formation of PEGylated gold nanoshell on the surface. PGsP NCs could not only provide excellent contrast enhancement for dual modal ultrasound and CT imaging in vitro and in vivo, but also serve as efficient photoabsorbers for photothermal ablation of tumors on xenografted nude mouse model. To our best knowledge, this is the first report of gold nanoshell serving as both CT contrast agents and photoabsorbers for photothermal therapy. The novel multifunctional nanomedicine would be of great value to offer more comprehensive diagnostic information to guide more accurate and effective cancer therapy.